Progress and technical points of transoral endoscopic thyroidectomy vestibular approach - CHEN Peng, SHI Jianing, JIA Wenjun, FANG Jing (Waike lilun yu shijian)
Transoral endoscopic thyroidectomy vestibular approach (TOETVA) is a novel endoscopic thyroid surgery method. TOETVA can completely dissect the lymph nodes in the central area and Ⅳ area. TOETVA has both advantages of beauty and curative effect. Based on the clinical experience of this technique, the author reviewed the development, indications, complications and surgical skills of TOETVA in recent years, and looked forward to the development trend of this technique.